2021
DOI: 10.1016/j.bbrep.2020.100876
|View full text |Cite
|
Sign up to set email alerts
|

A novel cysteine proteinase inhibitor from seeds of Enterolobium contortisiliquum and its effect on Callosobruchus maculatus larvae

Abstract: This study focused on the characterization of a novel cysteine proteinase inhibitor from Enterolobium contortisiliquum seeds targeting the inhibition of the growth of Callosobruchus maculatus larvae, an important cosmopolitan pest of the cowpea Vigna unguiculata during storage. The inhibitor was isolated by ion-exchange besides of size exclusion chromatography. EcCI molecular mass is 19,757 Da, composed of two polypeptide chains. It strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The functions of part‐specific genes reflect well‐known processes and pathways that are key to the physiology of each body part, such as fatty acid accumulation and response to maturation‐ and germination‐related phytohormones in seeds (abscisic acid and gibberellin, respectively) (Chauffour et al., 2019; Li et al., 2022; Ogawa et al., 2003), defense‐related genes in seed coats (Nunes et al., 2021; Shalovylo et al., 2021; Silva et al., 2018), nodulation‐related transporters and signaling components in root nodules (Banasiak et al., 2021; Niño‐González et al., 2019; Zeng et al., 2023), and photosynthesis‐ and plant growth‐related gene families in aerial parts (Jeena et al., 2019; Ren and Gray, 2015; Stortenbeker and Bemer, 2019). Collectively, our results validate the data reliability in the Soybean Expression Atlas v2.…”
Section: Resultsmentioning
confidence: 99%
“…The functions of part‐specific genes reflect well‐known processes and pathways that are key to the physiology of each body part, such as fatty acid accumulation and response to maturation‐ and germination‐related phytohormones in seeds (abscisic acid and gibberellin, respectively) (Chauffour et al., 2019; Li et al., 2022; Ogawa et al., 2003), defense‐related genes in seed coats (Nunes et al., 2021; Shalovylo et al., 2021; Silva et al., 2018), nodulation‐related transporters and signaling components in root nodules (Banasiak et al., 2021; Niño‐González et al., 2019; Zeng et al., 2023), and photosynthesis‐ and plant growth‐related gene families in aerial parts (Jeena et al., 2019; Ren and Gray, 2015; Stortenbeker and Bemer, 2019). Collectively, our results validate the data reliability in the Soybean Expression Atlas v2.…”
Section: Resultsmentioning
confidence: 99%
“…Proteinase inhibitors may play a role as reserve proteins in plants ( Richardson, 1991 ; Hansen et al, 2007 ) and be involved in plant defense mechanisms. Cysteine PIs were previously isolated from seeds of the Enterolobium contortisiliquum tree targeting larval growth inhibition in the pest Collasobruchus maculatus ( Nunes et al, 2021 ). Several studies have shown feeding insects with transgenic plants that express proteinase inhibitors to delay insect growth and development, and to cause starvation and death ( Koiwa et al, 1998 ; Schuler et al, 1998 ; Mosolov et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mean linear intercept (Lm) is the most-used parameter to demonstrate the presence of alveolar enlargement [17]. The reticulum with 50 lines (100 points) was coupled under an optical microscope (E200 MV, Nikon Corporation, Tokyo, Japan), and the analysis was performed by counting the intersections between the reticulum lines and the lung parenchyma.…”
Section: Lmmentioning
confidence: 99%
“…PI 0601390-2). Pep-3EcTI has eight amino acids in its composition, a molecular mass of 994.21 Da, and an isoelectric point of 9.75 [17].…”
Section: Introductionmentioning
confidence: 99%